2021
DOI: 10.1038/s41436-020-00979-w
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous truncating variants in SUFU cause congenital ocular motor apraxia

Abstract: Purpose This study aimed to delineate the genetic basis of congenital ocular motor apraxia (COMA) in patients not otherwise classifiable. Methods We compiled clinical and neuroimaging data of individuals from six unrelated families with distinct clinical features of COMA who do not share common diagnostic characteristics of Joubert syndrome or other known genetic conditions associated with COMA. We used exome sequencing to identify pathogenic variants and functional studies in patient-derived fibroblasts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 30 publications
4
27
0
Order By: Relevance
“…By including the two additional potential carriers, who are both female (the sister of UW423-1 and UW427-1 reported with COMA, and the mother of UW435-3 reported with macrocephaly), the male proportion among carriers could even drop to 25%. In the study by Schröder et al , 10 out of 13 (77%) manifesting carriers were male, while the only two clinically unaffected carriers were both female, in line with our observation 11. Such preponderance of male sex in manifesting versus non-manifesting carriers is intriguing, suggesting that sex-related factors may affect the penetrance of SUFU variants.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…By including the two additional potential carriers, who are both female (the sister of UW423-1 and UW427-1 reported with COMA, and the mother of UW435-3 reported with macrocephaly), the male proportion among carriers could even drop to 25%. In the study by Schröder et al , 10 out of 13 (77%) manifesting carriers were male, while the only two clinically unaffected carriers were both female, in line with our observation 11. Such preponderance of male sex in manifesting versus non-manifesting carriers is intriguing, suggesting that sex-related factors may affect the penetrance of SUFU variants.…”
Section: Resultssupporting
confidence: 90%
“…14 Interestingly, of the formerly reported 15 patients diagnosed with COMA and carrying heterozygous truncating SUFU variants, nearly all presented overlapping neurological features, including developmental and/or speech delay, early onset truncal and gait ataxia and, to a lesser extent, learning disability, indicating that these patients and the patients reported here are affected by the same neurodevelopmental condition related to SUFU haploinsufficiency. 11 Further supporting this observation, the imaging pattern is also highly consistent: indeed, all patients in this study as well as those reported by Schröder et al 11 showed a combination of vermis hypoplasia, superior cerebellar folial dysplasia and abnormalities of the SCPs, which variably appear long, thick and horizontal. This pattern often results in a 'mild MTS' appearance, similar to what has already been reported in patients with JS carrying pathogenic variants in other genes, including NPHP1, CPLANE1, CBY1 and FAM149B1 (figure 2M-P).…”
Section: Neurogeneticssupporting
confidence: 89%
See 3 more Smart Citations